The Environmental Degradation and Weak Law Enforcement in Illegal Mining Activities: A Juridicial Review - Fitriani; M. Ihsan; Mustafa Kamal; Hasanah Putri (International Journal of Law, Social Science, and Humanities, 2025)
IIlegal mining (PETI) has emerged as a significant threat to environmental sustainability and the conservation of natural resources in Indonesia. This study aims to examine the environmental damage caused by PETI. its impact on ecosystem functions and the shortcoming in legal enforcement within the mining sector. A normative juridical approach was employed, using statutory and international convention analysis, The findings reveal that PETI leads to deforestation, soil degradation,contamination from heavy mentals such as mercury and cyanide and the destruction of wildlife habitats in conservation areas. weak law enforcement, involvement of corrupt officials and lack of coordination among institutions exacerbate the situation. addressing PETI requires a comprehesive, strategy, including ecological reclamation, the development of environmentally based alternative livelihoods, community education, and regulatory reform. these measures are essential to establish a just and sustainable natural resource governance system and to uphold the constitutional right to a healthy environment;